Postural Balance Effects Associated with 400, 4000 or 10,000 IU Vitamin D3 Daily for Three Years: A Secondary Analysis of a Randomized Clinical Trial - Lauren A. Burt (Nutrients, 2020)
Vitamin D supplementation is proposed as a fall prevention strategy, as it may improve neuromuscular function. We examined whether three years of vitamin D supplementation (400, 4000 or 10,000 IU daily) affects postural sway in older adults. Three hundred and seventy-three non-osteoporotic, vitamin D-sufficient, community-dwelling healthy adults, aged 55−70 years, were randomized to 400 (n = 124), 4000 (n = 125) or 10,000 (n = 124) IU daily vitamin D3 for three years. Sway index was assessed at baseline, 12-, 24- and 36-months using the Biosway machine. We tested participants under four conditions: eyes open or eyes closed with firm (EOFI, ECFI) or foam (EOFO, ECFO) surfaces. Secondary assessments examined sway in the anterior-posterior (AP) and medio-lateral (ML) directions. Linear mixed effects models compared sway between supplementation groups across time. Postural sway under EOFO and ECFO conditions significantly improved in all supplementation groups over time. Postural sway did not differ between supplementation groups at any time under any testing conditions in normal, AP or ML directions (p > 0.05 for all). Our findings suggest that high dose (4000 or 10,000 IU) vitamin D supplementation neither benefit nor impair balance compared with 400 IU daily in non-osteoporotic, vitamin D-sufficient, healthy older adults.